2024
DOI: 10.1002/pbc.30872
|View full text |Cite
|
Sign up to set email alerts
|

Provider perspectives and recommendations on standardized sexual function screening intervention in adolescent/young adult oncology patients

Jenna Demedis,
Julia Reedy,
Eric J. Chow
et al.

Abstract: BackgroundSexual function (SF) concerns are common among adolescent and young adult (AYA) cancer survivors, are underrecognized and undertreated. This study sought AYA oncology provider input on the implementation of an SF screening tool to address this unmet need.ProcedureSemi‐structured interviews were completed with oncology providers (n = 25) who care for AYAs at a single institution. Interviews sought to understand barriers to addressing SF, elicit perspectives on use of an established screening tool, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 55 publications
(125 reference statements)
0
0
0
Order By: Relevance
“…Given the aforementioned barriers, which may be particularly salient in younger populations, our prior research evaluated the utility of using a patient-reported outcome measure for SD screening in AYA-CCS followed in pediatric settings (age 15–24 years), eliciting patient and provider perspectives in qualitative interviews [ 22 , 27 ]. Both groups were in favor of using a patient-reported outcome measure to address barriers and facilitate SD conversations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the aforementioned barriers, which may be particularly salient in younger populations, our prior research evaluated the utility of using a patient-reported outcome measure for SD screening in AYA-CCS followed in pediatric settings (age 15–24 years), eliciting patient and provider perspectives in qualitative interviews [ 22 , 27 ]. Both groups were in favor of using a patient-reported outcome measure to address barriers and facilitate SD conversations.…”
Section: Introductionmentioning
confidence: 99%
“…The SexFS Brief was found to be acceptable and useful, with demonstrated response process and content validity [ 27 ]. In addition to evaluating the utility of the SexFS Brief, patients and providers offered perspectives for how the SexFS Brief could be implemented into clinical use, including recommendations for delivery, results storage and review, and needed resources [ 22 , 27 ]. These recommendations were included in an SD screening intervention prototype that is being iteratively adapted in an ongoing phase of research.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations